Tích hợp các đại số gia tử cho suy luận ngôn ngữ - Khang, Trần Đình (Journal of Computer Science and Cybernetics, 2016)
In this paper, a method for aggregation of hedge algebras is proposed. It can be used for linguistic reasoning and building of linguistic data bases for any linguistic variable.